Regulation Formulation of AI Utilization in Indonesia: The Dilemma between Certainty and Utility to Realize Golden Indonesia Vision (Lex Scientia Law Review, 2026)
New regulation formulation methods are needed in the development and use of artificial intelligence (AI) in Indonesia. Therefore, this study aimed to argue how the current method of legislative development in Indonesia will need to consider the principles of legal certainty and utility for any future AI laws. These two principles were only elements of the puzzle that were influenced and shaped by other national and local policy needs, which needed considerations by the government. Different from previous investigations that primarily examined AI based on existing rules, this study attempted to provide a different perspective, namely, the dilemma between certainty and utility in formulating AI regulations. A legal-normative method was adopted, and relevant national strategies were analyzed. The results showed that the absence of comprehensive regulations on the use of AI caused legal uncertainty, while opening opportunities for innovation that were not balanced with an adequate ethical and accountability framework. Any AI law needed to balance the considerations with innovation and community protection. Indonesia should also adopt jurisdictions of AI law early, such as the European Union (EU) and the United States (US), as well as international institutions, to inform the development of policy and law. The result of this study was expected to bridge the dilemma between certainty and utility to realize the vision of Golden Indonesia 2045, which was adaptive, responsive, and distinctive through the mastery of ethical and responsible science and technology.